2007
DOI: 10.1021/ma071356z
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Driven Coassembly of a Diblock Copolymer and an Oppositely Charged Homopolymer in Aqueous Solutions

Abstract: Electrostatically driven coassembly of poly(acrylic acid)-block-poly(acrylamide), PAA-b-PAAm, and poly(2-methylvinylpyridinium iodide), P2MVP, leads to formation of micelles in aqueous solutions. Light scattering and small angle neutron scattering experiments have been performed to study the effect of concentration and length of the corona block (N PAAm ) 97, 208, and 417) on micellar characteristics. Small angle neutron scattering curves were analyzed by generalized indirect Fourier transformation and model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 26 publications
6
65
0
Order By: Relevance
“…The scaling behaviour of structural parameters such as micellar size and aggregation number with respect to, for example, core and corona block length, is sparsely investigated [6,7]. One may anticipate similar dependencies as the ones experimentally reported and theoretically derived for micelles consisting of polymeric amphiphiles.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The scaling behaviour of structural parameters such as micellar size and aggregation number with respect to, for example, core and corona block length, is sparsely investigated [6,7]. One may anticipate similar dependencies as the ones experimentally reported and theoretically derived for micelles consisting of polymeric amphiphiles.…”
Section: Introductionmentioning
confidence: 65%
“…The apparent micellar aggregation number, P agg , and more specifically, the number of anionic, P − agg , and cationic, P + agg polymers per micelle can be calculated from M micelle , M building block (see ref. [6] for the definition of a "building block"), and f + . Toluene was used as a reference.…”
Section: Static and Dynamic Light Scattering (Sls/dls)mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we would like to remark that these dependencies might be investigated quantitatively in for example Cryo-TEM experiments on a system where one of the coronal blocks could be stained selectively, which is not the case in the present system. Moreover, we suppose that a more symmetric PEO/PVOH system would consist of ellipsoidal Janus-micelles, as was found for the rather symmetric P2MVP 42 Consider a strict core-shell segregation where all PAA/ PVOH and P2MVP/PEO junctions are locked to the core/ corona interface, restricting the number of possible chain conformations. It is likely that the short cationic blocks are incapable of compensating all charges of the much longer anionic blocks, i.e., it would involve a considerable stretching penalty if at all possible, so that small, monovalent counterions are taken up by the micellar core to establish charge neutrality.…”
Section: Discussionmentioning
confidence: 97%
“…This concept has been explored in a series of recent papers [11,12,[24][25][26] where we observed that a pair of relatively miscible hydrophilic blocks yielded spherical C3Ms with a mixed shell and a pair of relatively immiscible hydrophilic blocks yielded ellipsoidal micelles with a laterally segregated corona (Janus-micelles). A combination of poly(2-(N,N-dimethylamino)ethyl methacrylate)-blockpoly(glyceryl methacrylate), PDMAEMA 45 -b-PGMA 90 and poly(acrylic acid)-block-poly(acrylamide), PAA 42 -bPAAm 417 resulted in spherical micelles with a mixed corona [11], while the Janus-type segregation was achieved in aqueous mixtures of poly(N-methyl-2-vinyl pyridinium iodide)-block-poly(ethylene oxide), P2MVP 42 -b-PEO 446 and poly(acrylic acid)-block-poly(acrylamide), PAA 42 -bPAAm 417 [12,24,25]. Within the corona of these micelles, the relatively immiscible PAAm and PEO blocks were approximately of equal size and abundance.…”
Section: Introductionmentioning
confidence: 99%